The Use of Hand Puppets as a Media for Developing Language Skills for Children Aged 4-5 Years: A Case Study at Dharma Wanita Puhpelem - Rahmadhani, Annisa Dwi; Fauziyah, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to examine the use of hand puppets as a medium to improve language skills, social interaction, and vocabulary in early childhood through role-playing activities. Methodology: The research used a descriptive qualitative method with a case study approach. Data were collected through observations, interviews with teachers, and analysis of documentation from learning activities. Results: The findings show that the use of hand puppets significantly improved the language skills of children aged 4–5 years, including speaking, listening, and effective communication. The children demonstrated greater enthusiasm in participating in activities involving hand puppets and showed increased self-confidence when speaking. Applications/Originality/Value: This study suggests that hand puppets are an effective, fun, and educational tool for developing early childhood language skills. Educators are encouraged to incorporate hand puppets into learning strategies to enrich children's language experiences from an early age.